Localization Patterns of Sumoylation Enzymes E1, E2 and E3 in Ocular Cell Lines Predict Their Functional Importance - Gong, Xiaodong; Nie, Qian; Xiao, Yuan; Xiang, Jia-Wen; Wang, Ling; Liu, Fangyuan; Fu, Jia-Ling; Liu, Yunfei; Yang, Lan; Gan, Yuwen; Chen, Huimin; Luo, Zhongwen; et al. (Current Molecular Medicine, 2018)
Purpose: It is well established now that protein sumoylation acts as an important regulatory mechanism mediating control of ocular development through regulation of multiple transcription factors. Yet the functional mechanisms of each factor modulated remain to be further explored using the available in vitro systems. In this regard, various ocular cell lines including HLE, FHL124, αTN4-1, N/N1003A and ARPE-19 have been demonstrated to be useful for biochemical and molecular analyses of normal physiology and pathogenesis. We have recently examined that these cell lines express a full set of sumoylation enzymes E1, E2 and E3. Following this study, here we have examined the localization of these enzymes and determined their differential localization patterns in these major ocular cell lines. Methods: The 5 major ocular cell lines were cultured in Dulbecco’s modified Eagle’s medium (DMEM) containing fetal bovine serum (FBS) or rabbit serum (RBS) and 1% Penicillin- Streptomycin. The localization of the 3 major sumoylation enzymes in the 5 major ocular cell lines were determined with immunohistochemistry. The images were captured with a Zeiss LSM 880 confocal microscope. Results: we have obtained the following results: 1) The sumoylation enzymes SAE1, UBC9 and PIAS1 are distributed in both nucleus and cytoplasm, with a much higher level concentrated in the nucleus and the neighboring cellular organelle zone in all cell lines; 2) The sumoylation enzyme UBA2 was highly concentrated in both cytoplasm membrane, cytoskeleton and nucleus of all cell lines; 3) The ligase E3, RanBP2 was exclusively localized in the nucleus with homogeneous distribution. Conclusions: Our results for the first time established the differential localization patterns of the three types of sumoylation enzymes in 5 major ocular cell lines. Our establishment of the differential localization patterns of the three types of sumoylation enzymes in these cell lines help to predict their functional importance of sumoylation in the vision system. Together, our results demonstrate that these cell lines can be used for assay systems to explore the functional mechanisms of sumoylation mediating ocular development and pathogenesis.
Keywords: RanBP2